Employer Fraud and Toxic Leadership and Collusion with PMC Operations: Implications for a Dual Metro Project in UP, India - Prof Dr Paul James (Journal of Management Research, 2025)
This research is concentrated on the opinions of a PMC/Engineer staff of a dual metro construction project in UP, India, in relation to project fraud and underpinned by toxic leadership of the Employer. The research study employed a qualitative/interpretive methodology focused on grounded theory to extract meaning associated with the views and practices regarding the Employer and PMC Core Group collusion to negatively affect the project performance and management competence. The research scope was PMC/Engineer staff as part of the joint venture, contracted by the Employer, to oversee the project management and construction. The targeted population was made up of eleven (11) respondents, from a Project Management JV (PMC), located across a dual metro construction project having similar experiences of toxic leadership and fraud. The research outcomes comprised of four (4) main-themes - Employer, PMC Core Group, PMC, and ED; with Fourteen sub-themes (14) – illustrated by 276 discussion targets. The research outcome has raised important issues of project Employer derived fraud, where toxic leadership was used to deflect from the fraudulent activities underpinned by a PMC Core Group, acting as sycophantic fraud “enablers”. These included harassment, creation of fear, arrogation of contract, and a sense of impunity of the Employer MD/DWI and the PMC Core Group. The lack of risk management and project governance, attributed to significant procedural failures of the project stakeholders, including the European donor, has raised clear evidence of ongoing and associated fraud.